2003
DOI: 10.1177/0886260502238537
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of a Treatment Program for Adult Sex Offenders

Abstract: McGrath et al. / OUTCOME OF A TREATMENT PROGRAMThis study examined the recidivism rates of 195 adult male sex offenders who were referred to a prison-based cognitive-behavioral treatment program. Of this sample, 56 participants completed treatment, 49 entered but did not complete treatment, and 90 refused treatment services. Although participants were not randomly assigned to treatment conditions, there were no between-group differences on participants'pre-treatment risk for sexual recidivism as appraised on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 15 publications
6
77
0
Order By: Relevance
“…The results of the study by McGrath, Cumming, Hoke and Lingston (2003) evaluating a Vermont Department of Corrections treatment programme for adult male sex offenders indicated that, men who complete cognitive-behavioural sex offender programmes sexually re-offend at relatively low rates. The number of sexual re-offenders in the completed treatment groups (5,4%) was significantly lower than that of the some treatment (30,6%) and no treatment groups (30%) (McGrath et al, 2003).…”
Section: Cognitive-behavioural Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study by McGrath, Cumming, Hoke and Lingston (2003) evaluating a Vermont Department of Corrections treatment programme for adult male sex offenders indicated that, men who complete cognitive-behavioural sex offender programmes sexually re-offend at relatively low rates. The number of sexual re-offenders in the completed treatment groups (5,4%) was significantly lower than that of the some treatment (30,6%) and no treatment groups (30%) (McGrath et al, 2003).…”
Section: Cognitive-behavioural Perspectivementioning
confidence: 99%
“…The number of sexual re-offenders in the completed treatment groups (5,4%) was significantly lower than that of the some treatment (30,6%) and no treatment groups (30%) (McGrath et al, 2003). A review of North American sexual offender programmes revealed that most were either cognitive-behavioural or any one form or another of multi-modal or eclectic psychotherapy (Brzecki & Wormith, cited in Marshall, 1999).…”
Section: Cognitive-behavioural Perspectivementioning
confidence: 99%
“…The media and political misrepresentations, along with the attention focused on the few violent offenders, causes the general public into believing that sex offenders are persistent; however, some of the reoffense data does not suggest this is the case (US DOJ, 1994;McGrath et al, 2003;Zimring et al, 2007;Garfinkle, 2003).…”
Section: Community Policing or Draconian Public Humiliationmentioning
confidence: 99%
“…Furthermore, the punitive aspect of notification laws and desires of sex offenders to avoid public humiliation have resulted in plea bargain agreements that subvert the stated reason for notification which may put the community at more risk (Freeman-Longo, 2000). Finally, exaggerated claims of high recidivism rates among sex offenders by activists are countered by data suggesting sex offenders have lower rates than the general criminal population (Sample and Bray, 2003;US DOJ, 1994, CSOM, 2002McGrath et al, 2003); however, sex offenders who do recidivate are more likely than other criminals to commit a new sex offense (Sample and Bray, 2003).…”
Section: Beyond Notificationmentioning
confidence: 99%
See 1 more Smart Citation